2015
DOI: 10.1039/c5ce00639b
|View full text |Cite
|
Sign up to set email alerts
|

Top-seeded solution growth and characterization of a Bi2Mo2.66W0.34O12single crystal

Abstract: ARTICLE This journal isSingle crystals of Bi 2 Mo 2.66 W 0.34 O 12 with dimensions up to 70 mm × 55 mm × 45 mm were successfully grown using a top-seeded solution growth (TSSG) method with MoO 3 -WO 3 mixture as a flux. The material crystallizes in the centrosymmetric space group P2 1 /c (No. 14), with unit cell parameters of a = 7.7212(8) Å, b = 11.4938(12) Å, c = 11.9970(12) Å, and β = 115.5070 (10)°. The as-grown crystal exhibits {100}, {010}, {011}, {110}, {021}, {012}, {120}, {-111}, {-102}, and {1-1-2} f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The bands observed at around 558 cm −1 and 512 cm −1 mostly come from the symmetric or asymmetric stretching vibration modes of Mo-O bonds, whereas those ranging from 150 to 300 cm −1 are likely assigned to the bending modes of the bridge Mo-O-Mo. 44,45 It is worth noting that β-LTM crystal exhibits high Raman intensity at 955cm −1 and the corresponding full-width at halfmaximum of Raman intensity was estimated and found to be 12.54 cm −1 , comparable to those of other molybdenum tellur- ite, 46 which is essential for achieving large Raman gain coefficients. Accordingly, such favorable Raman performance combined with the wide transparency region of β-LTM, make it a promising candidate for mid-IR Raman crystals.…”
Section: Raman Spectroscopymentioning
confidence: 82%
See 1 more Smart Citation
“…The bands observed at around 558 cm −1 and 512 cm −1 mostly come from the symmetric or asymmetric stretching vibration modes of Mo-O bonds, whereas those ranging from 150 to 300 cm −1 are likely assigned to the bending modes of the bridge Mo-O-Mo. 44,45 It is worth noting that β-LTM crystal exhibits high Raman intensity at 955cm −1 and the corresponding full-width at halfmaximum of Raman intensity was estimated and found to be 12.54 cm −1 , comparable to those of other molybdenum tellur- ite, 46 which is essential for achieving large Raman gain coefficients. Accordingly, such favorable Raman performance combined with the wide transparency region of β-LTM, make it a promising candidate for mid-IR Raman crystals.…”
Section: Raman Spectroscopymentioning
confidence: 82%
“…The bands observed at around 558 cm −1 and 512 cm −1 mostly come from the symmetric or asymmetric stretching vibration modes of Mo–O bonds, whereas those ranging from 150 to 300 cm −1 are likely assigned to the bending modes of the bridge Mo–O–Mo. 44,45…”
Section: Resultsmentioning
confidence: 99%
“…21,43 Bi 2 Mo 2.66 W 0.34 O 12 (BMO) crystallizes in the monoclinic system with the space group P2 1 /c and can be considered as a distorted scheelite structure with ordered cation vacancies. 44,45 Therefore, the BMO crystals are also a candidate for laser host materials. Previous research on the structure of Bi 2 Mo 3 O 12 , while BMO can be regarded as W 6+ partially substituted for Mo 6+ , has proved that Ce 3+ ions can occupy both the Bi 3+ sites and even the cation vacancies in the Bi 2 Mo 3 O 12 crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery and design of transition-metal oxides with special optoelectronic properties have received considerable interest and been extensively investigated in recent decades. Among numerous inorganic materials, molybdate oxide compounds are of utter importance in academic research and industrial applications owing to their capability of the photocatalysis, photoluminescence, nonlinear optical (NLO) frequency conversion, and excellent physicochemical stability. Notably, from a crystallographic perspective, molybdate oxides exhibit a rich structural chemistry and thus provide an impressive advantage in that desired material performances can be effectively regulated by arranging the fundamental building units, mainly including octahedral [MoO 6 ] and tetrahedral [MoO 4 ] structures. , Specifically, the structural building block [MoO 6 ] octahedra tend to be asymmetric coordination configurations originating from distinct second-order Jahn–Teller (SOJT) distortion among transition metals, resulting in a second harmonic generation (SHG) response . Accordingly, a series of molybdate oxides with [MoO 6 ] configurations have been successively synthesized, including BaTeMo 2 O 9 , Cs 2 TeMo 3 O 12 , Na 2 Te 3 Mo 3 O 16 , LiNa 5 Mo 9 O 30 , and KCsMoP 2 O 9 , emerging as promising second-order NLO crystals. Additionally, previous studies have definitively revealed that molybdate crystals with the structural motif [MoO 4 ] exhibit incomparable advantages on stimulated Raman scattering (SRS) due to the symmetrical vibrations of [Mo–O] molecular ionic groups, which facilitate a strong inherent Raman shift with narrow line width . Compared to the second-order NLO effects, SRS effects provide a simple and effective means to shift the laser radiation frequency to another spectral region without the consideration of prerequisites such as acentric structures and phase matching.…”
Section: Introductionmentioning
confidence: 99%
“…13−18 Additionally, previous studies have definitively revealed that molybdate crystals with the structural motif [MoO 4 ] exhibit incomparable advantages on stimulated Raman scattering (SRS) due to the symmetrical vibrations of [Mo−O] molecular ionic groups, which facilitate a strong inherent Raman shift with narrow line width. 19 Compared to the second-order NLO effects, SRS effects provide a simple and effective means to shift the laser radiation frequency to another spectral region without the consideration of prerequisites such as acentric structures and phase matching. Based on the above-mentioned advantages, a series of molybdate Raman crystals, especially those containing isolated [ attention, which crystallizes in the I4̅ 3d space group and is isomorphic to Ca 12 Al 14 O 33 (C12A7).…”
Section: ■ Introductionmentioning
confidence: 99%